2008
DOI: 10.1080/09658210802307695
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in remembering and inferring spatial distances

Abstract: The abilities of males and females to make spatial inferences were compared. Spatial inference is concerned with the ability to work out new spatial information from memory. In two experiments, participants had to study line drawings depicting shapes linked either by straight or meandering lines. Afterwards, they had to remember the straight-line distances or to infer the straight-line distances. Several spatial abilities were also assessed: perceptual discrimination, mental rotation, and visuo-spatial working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 49 publications
5
42
0
1
Order By: Relevance
“…Similarly, Astur et al (2004) found that women were as accurate as men at finding target locations when tested in a virtual radial maze, albeit slower. Consequently, the sex differences observed in speed and path length in Astur's study and in our study do not seem to be related to knowledge of target locations but instead must be related to other factors such as differences in navigational preferences (Dabbs, Chang, Strong, & Milun, 1998;Lambrey & Berthoz, 2007;Malinowski, 2001;Postma et al, 2004;Ruggiero, Sergi, & Iachini, 2008;Sandstrom, Kaufman, & Huettel, 1998;Saucier et al, 2002).…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, Astur et al (2004) found that women were as accurate as men at finding target locations when tested in a virtual radial maze, albeit slower. Consequently, the sex differences observed in speed and path length in Astur's study and in our study do not seem to be related to knowledge of target locations but instead must be related to other factors such as differences in navigational preferences (Dabbs, Chang, Strong, & Milun, 1998;Lambrey & Berthoz, 2007;Malinowski, 2001;Postma et al, 2004;Ruggiero, Sergi, & Iachini, 2008;Sandstrom, Kaufman, & Huettel, 1998;Saucier et al, 2002).…”
Section: Discussionmentioning
confidence: 86%
“…Executive functions are necessary to acquire, combine and select spatial strategies, to plan and monitor behavioral motor responses according to environmental requirements (Lithfous et al, 2013;Vasilyeva & Lourenco, 2012). Some evidence has indeed reported strong associations between egocentric encoding and executive functions (e.g., Borella, Carretti, & De Beni, 2008;Iachini et al, 2005;Lithfous et al, 2013;Ruggiero, Sergi, & Iachini, 2008;Sanders, Holtzer, Lipton, Hall, & Verghese, 2008; see also Cornoldi & Vecchi, 2003;Craik, 1986;Meneghetti, Fiore, Borella, & De Beni, 2011;Park, 2000). Similarly, in childhood, the capacity to efficiently use reference frames would occur at about 6 years or later (Nardini et al, 2008(Nardini et al, , 2009Vasilyeva & Lourenco, 2012), as a consequence of delayed maturation of hippocampus and surrounding areas and frontal lobes as proved by myelination process, gray matter reduction, synaptogenesis, and resting metabolism (e.g., Fuster, 2002;Lenroot & Giedd, 2006;Newcombe & Huttenlocher, 2003;Pfefferbaum et al, 1994;Tsujimoto, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…So far, age-related changes in basic visuospatial abilities, mental imagery and navigational abilities have been investigated (see Ruggiero et al 2008;Iachini et al 2005). Laboratory-based psychometric tasks, such as mental rotation, and more ecological tasks, such as directionfinding and map learning have been used (Barrash 1994;Wilkniss et al 1997;Kirasic 1991).…”
Section: Introductionmentioning
confidence: 99%